Organic chemistry I workbook for dummies - Winter, Arthur (Wiley, 2008)
From models to molecules to mass spectrometry - solve organic chemistry problems with ease. Got a grasp on the organic chemistry terms and concepts you need to know, but get lost halfway through a problem or worse yet, not know where to begin? Have no fear - this hands-on guide helps you solve the many types of organic chemistry problems you encounter in a focused, step-by-step manner. With memorization tricks, problem-solving shortcuts, and lots of hands-on practice exercises, you'll sharpen your skills and improve your performance. You'll see how to work with resonance the triple-threat alkanes, alkenes, and alkynes functional groups and their reactions spectroscopy and more! 100s of Problems! Know how to solve the most common organic chemistry problems. Walk through the answers and clearly identify where you went wrong (or right) with each problem. Get the inside scoop on acing your exams! Use organic chemistry in practical applications with confidence.